2009
DOI: 10.1089/acm.2008.0331
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Electrical Skin Resistance at Acupuncture Points in Healthy Humans

Abstract: This study shows that electrical skin resistance at APs can either be lower or higher compared to the surrounding area. The phenomenon is characterized by high short-term and low long-term reproducibility. Therefore, we conclude that APs might possess specific transient electrical properties. However, as the majority of the measured APs did not show a changed ESR, it cannot be concluded from our data that electrical skin resistance measurements can be used for acupuncture point localization or diagnostic/thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 19 publications
(31 reference statements)
1
31
0
Order By: Relevance
“…In a previous investigation we showed that the results of this method were reproducible and that some, but not all, APs possess the claimed electrical properties. 18 We hypothesised that surgical intervention forms a considerable stimulus that would be refl ected by changes in ESR at the corresponding AP. We also considered whether the type of surgical intervention might affect the type of change (eg, one type of surgery resulting in a decreased ESR while another leads to an increased ESR).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous investigation we showed that the results of this method were reproducible and that some, but not all, APs possess the claimed electrical properties. 18 We hypothesised that surgical intervention forms a considerable stimulus that would be refl ected by changes in ESR at the corresponding AP. We also considered whether the type of surgical intervention might affect the type of change (eg, one type of surgery resulting in a decreased ESR while another leads to an increased ESR).…”
Section: Introductionmentioning
confidence: 99%
“…Some groups tried to control the effect of pressure on the electrode by applying same pressure on each electrode during measurements. For example Kramer et al used a blood pressure cuff to control and put the pressure on all probes (Kramer et al, 2009;Kramer et al, 2008). In our study, pressure didn't have any statistically significant effect on the measurements which is a major advantage of the device used in our research.…”
Section: Exfoliationmentioning
confidence: 59%
“…Figure 6 shows electrical skin impedance results of Shousanli (LI10) before and after exfoliation. Researches, two-electrode devices have been used (Kramer et al, 2009;Matsumoto et al, 1973). Many studies tried to find the relation between electrical skin impedance results and acupoints and meridians while others tried to find a relation between electrical skin impedance results of special acupoints and diseases (Matsumoto and Hayes, 1973;Oleson et al, 1980;Yuangen et al, 2001).…”
Section: Exfoliationmentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly larger needle grasp [18] and larger blood supply into the microvascular beds [19] at APs when compared to other areas has been observed. Additionally, conflicting results also exist about APs being spots characterized by a high density of neural receptors [20,21] or a distinct electrical skin resistance [22][23][24]. The fact that results of experimental as well as clinical research often appear multifarious and controversial might in part be due to technical challenges and shortcomings of the respective research projects [25].…”
Section: Introductionmentioning
confidence: 99%